Blank canvas. Volume 5, My so-called artist's journey - Higashimura, Akiko; MacFarlane, Ysabet Reinhardt (Seven Seas, 2020)
"High schooler Akiko has big plans to become a popular mangaka before she even graduates, but she needs to get much better at drawing if she ever wants to reach her goal. Looking for an easy fix, she signs up for an art class, thinking all her problems will soon be solved. She's in for a surprise: her new instructor is a sword-wielding taskmaster who doesn't care about manga one bit. But maybe this unconventional art teacher is just what she needs to realize her dreams!"--Provided by publisher.